Case report: Multiple biventricular aneurysms in arrhythmogenic cardiomyopathy - Lin, Jiadong; Lu, Zhijuang; Lin, Mingqin; Wan, Ying; Li, Jianfeng; Huang, Xinsheng (Frontiers in Cardiovascular Medicine, 2023)
Arrhythmogenic cardiomyopathy (ACM) is a genetic disease characterized by fibro-fatty myocardial replacement, clinically associated with malignant ventricular arrhythmias and sudden cardiac death. Complex clinical presentation and multiparametric diagnostic scoring system encompassing structural, histological, electrocardiographic, make ACM have a major challenge of diagnosis and therapy. Here, we reported a 57-year-old man with history of palpitation and premature ventricular contractions (PVC) who experienced syncope and sustained ventricular tachycardia with 213 heart rate and was successfully rescued by synchronized cardioversion. Echocardiography and high-frequency ultrasound showed multiple ventricular aneurysms in right ventricular free wall and a left ventricular apical region with mild biventricular systolic dysfunction. He and his 24-year-old daughter of genetic analysis found mutation site in the desmoplakin gene, chr6-7585274-7585275, NM_004415, exon24, c.7780delT (p.S2594Pfs*9), heterozygous, and likely pathogenic mutation. Withβ-blocker (bisoprolol) therapy, he did not experience syncope and presyncope symptoms during 21 months followup. Among the multimodality imaging of ACM, it is generally agreed that late gadolinium enhancement on cardiac magnetic resonance (CMR) is a more objective indicator of myocardial fibrosis. The primary, and most sensitive, clinical signs of desmoplakin cardiomyopathy are left ventricular systolic dysfunction, fibrosis on CMR, and frequent PVC. However, the echocardiography, especially high-frequency linear ultrasound, could clearly demonstrate the focal ventricular aneurysm and abnormal ventricular movement of right ventricular anterior free wall and apical region near the transducer.